Delayed cytopathicity of a feline leukemia virus variant is due to four mutations in the transmembrane protein gene. - Thomas, E (1993)
Two molecularly cloned, replication-defective variants of feline leukemia virus, called 61B and 61C, have both been shown to cause fatal immunodeficiency in cats when coinfected with a replication-competent, minimally pathogenic helper virus, but 61B exhibits a longer latency period between infection and disease (J. Overbaugh, E. A. Hoover, J. I. Mullins, D. P. W. Burns, L. Rudensey, S. L. Quackenbush, V. Stallard, and P. R. Donahue, Virology 188:558-569, 1992). Infection of the 3201 feline T-cell line with 61B plus helper virus also results in longer time from infection to cytopathic effect compared with 61C plus helper virus, providing an in vitro system with which to study the mechanism for this difference. We report that the primary determinant of cytopathicity of 61B maps to gp70, the extracellular envelope glycoprotein. The long latency of 61B, on the other hand, maps to the extracellular portion of the envelope transmembrane protein, in which there are only four predicted amino acid differences between 61B and 61C. These differences render 61B replication defective, and two of the predicted amino acid changes lie in a region that is highly conserved among many retroviruses. The eventual onset of 61B cytopathicity in cell culture was associated with the outgrowth of an apparent recombinant virus that encodes the pathogenic gp70 of 61B and replaces the transmembrane protein of 61B with that of the helper virus. Thus, during in vitro infection, a cytopathic virus evolved from a replication-defective virus and a nonpathogenic virus, suggesting that recombination between multiple variants in natural infection may influence progression of feline leukemia virus-associated immunodeficiency disease.